Becker meets Ricardo: Multisector matching with social and cognitive skills - Robert J. McCann; Xianwen Shi; Aloysius Siow; Ronald P. Wolthoff (Institute for the Study of Labor (IZA), 2012)
This paper presents a tractable framework for studying frictionless matching in school, work, and marriage when individuals have heterogeneous social and cognitive skills. In the model, there are gains to specialization and team production, but specialization requires communication and coordination between team members, and individuals with more social skills communicate and coordinate at lower resource cost. The theory delivers full task specialization in the labor and education markets, but incomplete specialization in marriage. It also captures well-known matching patterns in each of these sectors, including the commonly observed many-to-one matches in firms and schools. Equilibrium is equivalent to the solution of a utilitarian social planner solving a linear programming problem.
urn:nbn:de:101:1-2012081612244
Keywords: E24; J12; J24; J31; 330; social skill; cognitive skill; matching; sorting; education; labor; marriage; social welfare; linear programming; Kognition; Matching; Schule; Arbeitsgruppe; Ehe; Soziale Wohlfahrtsfunktion; Mathematische Optimierung; Theorie